Living with Tiny Aliens : the Image of God for the Anthropocene - Pryor, Adam (Groundworks (New York, N.Y.), 2020)
Living with Tiny Aliens imagines in theological terms how an individuals' meaningful existence persists within a cosmos pregnant with living-possibilities. In doing so, it works to articulate an astrobiological humanities.